The use of pragmatic markers by english speaking learners of brazilian portuguese - Schepers, Bruna Milano (2021)
The teaching and learning of Portuguese as an Additional Language (PAL) has achieved a place of great importance among researchers in the area. Thus, in view of the lack of studies referring to oral language in PAL, as well as the use of Pragmatic Markers (PMs) by speakers of additional languages, the purpose of this research is to collect informal speech data within the academic context in order to characterize the use of PAL markers. It is broadly known that studies on PMs have gained more attention in the last decades. One reason for this is the technological evolution in the area of Corpus Pragmatics and the countless benefits that the areas of Corpus Linguistics and Pragmatics can offer each other (ROMERO-TRILLO, 2018; AIJMER and RÜHLEMANN, 2015). Despite this, we have observed that there are still few studies on PMs and their uses in Brazilian Portuguese, as well as a gap with regards to the materials that explicitly teach this important aspect of spoken language. This research, therefore, will be based on the methodological principles of Corpus Pragmatics and the method of Contrastive Interlanguage Analysis (GRANGER, 2015). Data were collected from informal face-to-face and online interviews with foreign students, learners of PAL in the UK. Analysis of the data in comparison to a reference corpus suggests that the use of some markers may have been the result of transfer from the first and/or other additional languages. The compilation of an oral learner corpus of additional language is extremely relevant to the area of specialized studies on, for example, PAL or English as an Additional Language, and offers numerous possibilities for pedagogical application, in addition to contributing to the creation of pedagogical material that may help, in the realm of PMs, the learner to overcome possible pragmatic problems of language use.